1992
DOI: 10.1366/0003702924125618
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Characterization of Fe/Al2O3 Catalysts. Part I: Oxidic Precursors

Abstract: The structure of a series of Fe/Al2O3 catalysts containing from 1 to 24 weight percent iron has been examined by XRD, EXAFS, Mössbauer, ESCA, and gravimetric analysis. Two iron phases, Fe2O3 and Fe+3 in solid solution in the alumina support, are characterized as a function of iron loading. The combination of ESCA H2 titration and gravimetric analysis allows both quantitative and qualitative measurement of the two species. The amount of Fe2O3 phase increases with increasing iron loading for Fe1 to Fe24, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…Of note, the authors also estimated the theoretical coverage of 0.13 g per 100 m 2 Al 2 O 3 or ∼11 Fe atoms nm –2 to form monolayer coverage. Similarly, other studies also suggested that iron can be dispersed between 4 and 5.5 Fe atoms nm –2 over γ-Al 2 O 3 support. , Accordingly, the XRD and PDF results in this work indicate the possibility of forming a highly dispersed Fe-phase. Notably, temperatures higher than 1000 °C are usually required to form aluminate spinel (FeAlO 3 ) or crystalline hercynite (FeAl 2 O 4 ) from Fe 2 O 3 and Al 2 O 3 . , The XRD patterns of the Fe/Al 2 O 3 -S1 catalysts after one complete PDH cycle (Figure S2d) with H 2 S cofeed were also acquired.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Of note, the authors also estimated the theoretical coverage of 0.13 g per 100 m 2 Al 2 O 3 or ∼11 Fe atoms nm –2 to form monolayer coverage. Similarly, other studies also suggested that iron can be dispersed between 4 and 5.5 Fe atoms nm –2 over γ-Al 2 O 3 support. , Accordingly, the XRD and PDF results in this work indicate the possibility of forming a highly dispersed Fe-phase. Notably, temperatures higher than 1000 °C are usually required to form aluminate spinel (FeAlO 3 ) or crystalline hercynite (FeAl 2 O 4 ) from Fe 2 O 3 and Al 2 O 3 . , The XRD patterns of the Fe/Al 2 O 3 -S1 catalysts after one complete PDH cycle (Figure S2d) with H 2 S cofeed were also acquired.…”
Section: Resultssupporting
confidence: 81%
“…6 For 15 Fe/Al 2 O 3 , a satellite peak at 650 °C was observed which may be due to the formation of a minority 3D-Fe 2 O 3 species due to the higher coverage. 30,50,51 This is consistent with XAS results presented in section 3.3, which indicates some agglomeration at higher Fe loading. From Figure 5b, it is observed that the peak temperature (Tp) of the supported Fe oxide species appears to be relatively independent of Fe loading over Al 2 O 3 .…”
Section: X-ray Absorption Spectroscopysupporting
confidence: 91%
See 2 more Smart Citations
“…The Fe 3+ and Al 3+ ions have a very similar radius (the radius for Fe 3+ is 0.55Å, and that of Al 3+ is 0.54 Å, in an octahedral coordination), so it is not surprising, that, in the process of calcination, Fe 3+ cations can incorporate into the octahedral vacancies on the surface or subsurface of Al 2 O 3 substrate to form a kind of solid solution at the interface. This phenomenon is reported by a number of authors. For example, Carbucicchio 25 observed the formation of the surface solid solution of aluminum and iron oxide on the surface of alumina heated at 1100 °C by Mössbauer spectra. Vaishnava et al observed the same phenomenon for η-Al 2 O 3 , and Vuurman 27 for γ-Al 2 O 3 .…”
Section: Resultsmentioning
confidence: 59%